REMOTE AUDIT DAN INTEGRITAS AUDITOR SEBAGAI PENENTU KUALITAS AUDIT DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI (Studi Kasus pada Audit Eksternal di DKI Jakarta) - Putriku Hanna Puang; Anis Chariri (Diponegoro Journal of Accounting, 2025)
Digital transformation has driven significant changes in audit practices, especially with the increasing use of remote audits. This study aims to analyze the effect of remote audit and auditor integrity on audit quality, with task complexity as a moderating variable. Data were obtained from 118 auditors at the DKI Jakarta Public Accounting Firm (KAP) through an online questionnaire. Tests were conducted using the moderated regression method (MRA) using SPSS. The results show that remote audit and auditor integrity have a positive effect on audit quality. However, task complexity proved to weaken the relationship between the two independent variables on audit quality. This research contributes to the development of digital audit strategies and the strengthening of auditors' professional ethics in the context of complex tasks.